Acute and Short-Term Autonomic and Hemodynamic Responses to Transcranial Direct Current Stimulation in Patients With Resistant Hypertension - Rodrigues, Bruno; Barboza, Catarina A.; Moura, Eliezer G.; Ministro, Gabriela; Ferreira-Melo, Silvia E.; Castaño, Javier B.; Nunes, Wilton M. S.; Mostarda, Cristiano; Coca, Antonio; Vianna, Lauro C.; Moreno-Junior, Heitor (Frontiers in Cardiovascular Medicine, 2022)
Previously, we demonstrated that acute transcranial direct current stimulation (tDCS) reduced blood pressure (BP) and improved autonomic modulation in hypertensives. We hypothesized that acute and short-term tDCS intervention can promote similar benefits in resistant hypertensive patients (RHT). We assessed the impact of one (acute intervention) and ten (short-term intervention) tDCS or SHAM (20 min, each) sessions on BP, pulse interval (PI) and systolic blood pressure variabilities, humoral mechanisms associated with BP regulation, and cytokines levels. True RHT subjects (n = 13) were randomly submitted to one and ten SHAM and tDCS crossing sessions (1 week of “washout”). Hemodynamic (Finometer®, Beatscope), office BP, and autonomic variables (accessed through spectral analysis of the pulse-to-pulse BP signal, in the time and frequency domain – Fast Fourrier Transform) were measured at baseline and after the short-term intervention. 24 h-ambulatory BP monitoring was measured after acute and short-term protocols. Acute intervention: tDCS reduced BP, cardiac output, and increase high-frequency band of PI (vagal modulation to the heart). Short-term protocol: tDCS did not change BP and cardiac output parameters. In contrast, central systolic BP (−12%), augmentation index (−31%), and pulse wave velocity (34%) were decreased by the short-term tDCS when compared to SHAM. These positive results were accompanied by a reduction in the low-frequency band (−37%) and an increase of the high-frequency band of PI (+62%) compared to SHAM. These findings collectively indicate that short-term tDCS concomitantly improves resting cardiac autonomic control and pulse wave behavior and reduces central BP in RHT patients, https://ensaiosclinicos.gov.br/rg/RBR-8n7c9p.